Overlaps Between the Family and The Business: Key Insights and Challenges of Family Entrepreneurship in Portugal - Ana Paula MARQUES1; Ana Isabel COUTO (Communications of International Proceedings, 2020)
Family-oriented companies are a predominant type of company in the context of the Portuguese private business fabric. At the heart of this business typology, two structural aspects of the life of individuals coexist: work (company) and family, with multiple challenges experienced by those who create, manage and coordinate them: their entrepreneurs. Recent studies reveal that 50% of family businesses do not reach the second generation and only 20% reach the third generation (AEP, 2011). Business succession planning represents one of the main management challenges experienced in this segment of companies. This communication presents a reflection on family entrepreneurship in Portugal, offering a portrait of the family businesses in the North Region of Portugal and focusing on main management challenges, such as business succession and management professionalization. For this purpose, the main results from the research project “Roadmap for Portuguese family businesses” (2016-2018), financed by NORTE 2020 / FEDER will be presented. The aims of this project were to contribute to a better knowledge and institutional visibility of this segment of companies, as well as to assess the impact of companies Northern Region in the local, national and international economy.  The data presented is the result of an eclectic methodological design that has combined a quantitative-extensive approach, based on the construction of a database with all family companies formally registered in the North of Portugal and posteriorly the application of an online survey (LimeSurvey platform) to the family entities collected in previous step, in order to better characterise the profiles of family companies, and also a qualitative-intensive approach based on the conduction of a set of 23 in-depth interviews to family managers/ owners, bearing in mind the diversity of this business typology, namely in terms of basic variables such as the sector of activity, size, year of foundation, founder’s gender.
Keywords: Portugal; Family Entrepreneurship; Management Challenges; Entrepreneurs.